ECONOMIC POLICIES INSTRUMENTS USED BY DEVELOPED AND EMERGING STATES IN THE CONJUNCTURE OF OUR DAYS - Emilia Cornelia STOICA; Mihaela SUDACEVSCHI (Challenges of the Knowledge Society)
The objectives of economic policies that public authorities want to implement are economic growth and the improvement of the quality of life of the community members they lead. The success of this approach is ensured by the use of fiscal-budgetary and monetary policy instruments appropriate to both the aims pursued and the correlation with the economic and social conjuncture that characterizes the implementation period. These instruments refer to the tax system - the regulatory, procedural and administrative framework; budget expenditure system, in terms of structure and prioritization; public debt management; the monetary system, referring primarily to the management of inflation, interest rates, lending policy of the national economy sectors, etc. From the multitude of economic policy tools that have been used over time, with better or worse results, public authorities are developing policies that can fit into one of the following categories: expansionist, restrictive, protectionist, opening up to the market free, and so on. Applying these instruments to the real economy of a country will generate the hoped results if the appropriate conjunctural conditions are met both within and outside the country, which requires a thorough analysis of the macroeconomic and social development level of the concerned country as well as its position towards partners and neighbors, both from the point of view of commercial and / or investment relationships or political and strategic influence. Identifying the factors that influence the performance of fiscal and monetary policy implementation in each country is a key element as it can be used as a lever for future policy making. Any activity involves risks, and for each instrument of financial and monetary policy specific risks can be highlighted, which requires their isolation and proposing appropriate measures to address potential risk situations so that they do not negatively affect the overall result.